Exploring The Influences of Artificial Intelligence Tools on Students’ Self-Efficacy in Writing the Final Research Report - Utami, Andini Putri; Mahmud, Murni; Sunra, La (Indonesian Journal of Educational Studies, 2025)
Abstract. Many students feel less self-efficacy in their writing abilities, especially in producing writing that meets academic standards. Bad previous experiences often influence one's approach to writing academic assignments. As a result, students tend to feel anxious, demotivated, or even experience writer's block, which can delay their progress on the final research report. This study examines the impact of artificial intelligence tools on students’ self-efficacy in writing their final research report. This research employed a qualitative approach, utilizing interviews and documentation analysis involving six undergraduate students who completed their final research report using artificial intelligence tools. Findings suggest that utilizing artificial intelligence tools, such as ChatGPT, Grammarly, and DeepL, in the writing of the final research report can enhance students’ self-efficacy. The conclusion affirms that AI tools not only impacts the quality of the writing produced as the medium in the digital era and education, but also the internal processes that shape students' self-efficacy and behaviors in academic writing. Keywords: Self-Efficacy; Artificial Intelligence; Undergraduate Students; Influences; Final Research Report